Pathogenesis and histological changes of nephropathy associated with COVID‐19. Issue 1 (25th November 2022) - Lin, Lirong; Deng, Junhui; Tan, Wei; Li, Jie; Wu, Zhifeng; Zheng, Luquan; Yang, Jurong
Abstract: Coronavirus disease 2019 (COVID‐19) can cause damage to multiple organ, not only to the lungs, but also to the kidneys. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) can cause acute and chronic kidney disease through direct viral infection, indirect injury, and vaccination‐related injury. Like lung injury, kidney injury is also an important aspect affecting the severity and prognosis of SARS‐CoV‐2. This article summarizes the pathogenesis, pathological manifestations, and clinical features of SARS‐CoV‐2 direct or indirect renal injury. Including direct injury, indirect injury, special comorbidities (receiving kidney transplantation and chronic kidney disease), and vaccine‐related renal injury, and exploring the possible therapeutic effect of anti‐SARS‐CoV‐2 therapy on renal injury. The purpose is to provide reference for understanding COVID‐19‐related renal injury, guiding clinical and pathological diagnosis and treatment, and evaluating prognosis.